Architecture of distributed geoinformation technology for snow cover monitoring in circumstances of limited telecommunications accessibility - Yu. V. Belysheva; D. D. Sutyagin; E. S. Zimina (Российский технологический журнал)
Objectives. Snow cover has a complex multifactorial impact on the environment as a link between global climatic processes and the system of the Earth’s surface. Snow cover monitoring is one of the key tasks of hydrometeorology which also requires the systematic regular collection of its indicators. This work aims to develop an architecture of geoinformation technology for snow cover monitoring with the purpose of addressing the problem of automating the collection of snow cover indicators and their further maintenance. This architecture can also be used for other hydrometeorological monitoring tasks.Methods. This paper analyzes the existing fundamental basis of snow cover data collection and uses the method of systems approach to describe the architecture of distributed geoinformation technology.Results. The paper presents an architecture of distributed geoinformation technology focused on snow cover monitoring from measurements, data aggregation, and validation to their transfer to a centralized processing system. A prototype of portable user terminal modules for testing this technology is developed.Conclusions. The proposed architecture is capable of functioning in circumstances of limited telecommunication availability, while ensuring data integrity control and personalization of responsibility by introducing an electronic signature of each measurement session. This architecture can be expanded by developing and implementing modules for other types of measurements.